Role of IL‐28B and inosine triphosphatase polymorphisms in efficacy and safety of Peg‐Interferon and ribavirin in chronic hepatitis C compensated cirrhosis with and without oesophageal varices. Issue 2 (25th July 2012) - Di Marco, V.; Calvaruso, V.; Grimaudo, S.; Ferraro, D.; Pipitone, R. M.; Di Stefano, R.; Craxì, A.
Abstract : Summary. Genetic factors can influence the outcome of antiviral therapy in chronic hepatitis C (HCV). We evaluated the role of interleukin‐28B single nucleotide polymorphisms (SNPs) and inosine triphosphatase (ITPA) gene variants in HCV cirrhosis treated with Peg‐Interferon and ribavirin. A prospective cohort of 233 patients with compensated cirrhosis received 1–1.5 μg/kg/week of Peg‐Interferon alpha‐2b plus 1000–1200 mg/day of RBV for 48 weeks. A sustained virologic response (SVR) was achieved in 27% of patients. On multivariate logistic analysis, the absence of oesophageal varices (OR 3.64 CI 95% 1.27–10.44 P = 0.016), infection with genotype 2 or 3 (OR 4.06, CI 95% 1.08–15.26, P = 0.038), C/C alleles of rs12979860 SNP (OR 7.04, CI 95% 2.40–20.72, P < 0.001) and rapid virologic response (RVR) (OR 78.29, CI 95% 16.07–381.29, P < 0.001) were independently associated with SVR. Patients who experienced post‐treatment relapse received lower total doses of Peg‐Interferon (52.0 ± 15.8 μg/kg vs 65.7 ± 13.3 μg/kg, P < 0.001) and lower total dose of RBV (3829 ± 1210 mg vs 4709 ± 954 mg, P < 0.001) than patients who achieved an SVR. ITPA variants predictive of high ITPase activity were associated with reduction of haemoglobin ≥3 g/dL in the first 4 weeks ( P < 0.001), and with reduction of haemoglobin <10 g/dL ( P = 0.03) on treatment. In conclusion, combination therapy with Peg‐Interferon and RBV in patients with HCV cirrhosis must be guided by virus genotype, severity of portal hypertension, favourable IL‐28B polymorphisms and ITPA variants, and RVR on treatment.